Homoeopathic Management of Chronic Mastitis – A Case Report (Advancements in Homeopathic Research, 2024)
Mastitis is characterized by inflammation in the  breast, which may or may not be associated with  an infection. While it typically occurs in women of  childbearing age, it can manifest in individuals of all  age groups, including males. In this case report we present a case of chronic  mastitis, presenting with complaints of severe pain  in left breast with inflammation and pus formation  present on lateral side. Pain aggravated on motion  and touch. After complete case taking and proper  repertorisation than on the basis of totality of  symptoms Phytolacca decandra 200 was prescribed.
Keywords: Homoeopathy; Mastitis; Phytolacca decandra